Biodegradable antimicrobial films based on poly(lactic acid) matrices and active azo compounds. Issue 33 (11th May 2015) - Concilio, Simona; Iannelli, Pio; Sessa, Lucia; Olivieri, Rita; Porta, Amalia; De Santis, Felice; Pantani, Roberto; Piotto, Stefano
ABSTRACT Using solvent casting and melt compounding methods, we realized antibacterial and antifungal poly(lactic acid)‐based films by introducing different percentages of antimicrobial azo dyes into polymer matrices. Concentration up to 0.01% (w/w) of azo compounds permitted the preparation of antimicrobial and transparent films. The thin films retained the properties of the pure PLA matrices, such as glass transition temperature, flexibility, and amorphous nature. The films exhibited antimicrobial activity and the capability to inhibit biofilms formation of Staphylococcus aureus and Candida albicans. Spectrophotometric investigation of azo compounds release from the polymer matrices confirmed that the materials might have applications in fields where an intrinsic antimicrobial ability of the material is required, such as biomedical tools, biodegradable antibacterial coatings, and films for active packaging. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42357.